The responses of soil microbial characteristics to nitrogen addition and biochar amendment in a Larix kaempferi plantation - Hu, Chen; Ma, Zhiyuan; Gong, Jinyu; Lei, Jingpin; Cui, Hongxia (Frontiers in Ecology and Evolution, 2023)
Nitrogen (N) deposition is an important environmental factor that can change soil chemical properties. It can also alter the characteristics of microbial communities. The incorporation of biochar into soils is considered a potential strategy to enhance carbon (C) storage in soil and modify the impacts of N deposition. However, the impacts of biochar on the microbial characteristics of soil after short-term N deposition in subtropical plantations remain poorly understood. Here, we investigated the effects of biochar application (0, 5, 10 t ha−1) on soil chemical traits and microbial characteristics (extracellular enzyme activities, microbial community and microbial biomass) in a Larix kaempferi plantation in Shennongjia, China, under N addition (0, 50, 100 kg N ha−1 yr−1) during two growing seasons. We found that simulated N deposition significant increased soil total nitrogen (TN), nitrate nitrogen (NO3−-N) and total phosphorus (TP) concentrations, while heavy N deposition (100 kg N ha−1 yr−1) significant decreased soil microbial biomass nitrogen (MBN) concentration and β-glucosidase (β-GC) activity. Biochar amendment significantly increased soil microbial biomass, TN and soil organic carbon (SOC) concentrations. Both N addition and biochar amendment significantly altered Ascomycota and Basidiomycota relative abundance, with biochar amendment increasing Ascomycota relative abundance and decreasing Mortierellomycota relative abundance under heavy N deposition. Fungal diversity showed a positive correlation to TN, TP and NO3−-N concentrations, but a negative correlation to MBN. Biochar addition inhibited the increase in soil NO3−-N concentration caused by high N addition in the plantation, and influenced the change in the composition of microbial community caused by N addition. Our piecewise structural equation model suggested that N addition affected MBN and fungal diversity directly or indirectly via its effects on soil enzyme activities and properties. In contrast, there were no significant direct or indirect effects on bacterial diversity among all factors. These results improve our understanding of the influence and mechanisms of N addition and biochar amendment on soil microbial characteristics in subtropical coniferous plantations in the short term, and can provide a valuable reference for predicting the future effects of N deposition on soils in this region’s plantation.